Operating characteristics of the electrostatic monitors of elliptic, rectangular and circular cross-section - Ivashchenko, V.E.; Karnaukhov, I.M.; Trotsenko, V.I.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2004)
The various methods of approximation of operating characteristics of electrostatic beam position monitors were investigated. The new method that allows on order to increase the precision of approximation of horizontal coordinate is found. The simulation of measurement of frequencies of betatron oscillations is carried out.